2018
DOI: 10.3389/fimmu.2018.01097
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing–Remitting Multiple Sclerosis Is Characterized by a T Follicular Cell Pro-Inflammatory Shift, Reverted by Dimethyl Fumarate Treatment

Abstract: Multiple sclerosis (MS) is considered a T cell-mediated autoimmune disease, although several evidences also demonstrate a B cell involvement in its etiology. Follicular T helper (Tfh) cells, a CXCR5-expressing CD4+ T cell subpopulation, are essential in the regulation of B cell differentiation and maintenance of humoral immunity. Alterations in circulating (c)Tfh distribution and/or function have been associated with autoimmune diseases including MS. Dimethyl fumarate (DMF) is a recently approved first-line tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 38 publications
5
28
1
Order By: Relevance
“…High level of Th2-like and Th17-like CXCR5 + CD4+ T cells was shown in patients with juvenile dermatomyositis 30 , in SS 39 . Moreover, the imbalance in circulating Tfh cell subsets was founded in multiple sclerosis patient's peripheral blood and it was closely related to the increase of "pro-inflammatory" Tfh17.1 cells and decrease of Th1-like Tfh cells 41,42 . Thus, the frequency of Th2 was significantly higher, while Tfh1 cells were lower in blood samples from patients with active SLE (SLEDAI score > 8) if compared with HC 43 .…”
Section: Discussionmentioning
confidence: 99%
“…High level of Th2-like and Th17-like CXCR5 + CD4+ T cells was shown in patients with juvenile dermatomyositis 30 , in SS 39 . Moreover, the imbalance in circulating Tfh cell subsets was founded in multiple sclerosis patient's peripheral blood and it was closely related to the increase of "pro-inflammatory" Tfh17.1 cells and decrease of Th1-like Tfh cells 41,42 . Thus, the frequency of Th2 was significantly higher, while Tfh1 cells were lower in blood samples from patients with active SLE (SLEDAI score > 8) if compared with HC 43 .…”
Section: Discussionmentioning
confidence: 99%
“…[98][99][100][101][102][103][104] A very interesting question is why Tfh cells are specifically involved in the destruction of islet β cells but not other organs in T1D patients. [98][99][100][101][102][103][104] A very interesting question is why Tfh cells are specifically involved in the destruction of islet β cells but not other organs in T1D patients.…”
Section: Perspectivementioning
confidence: 99%
“…The increase of Tfh cells has been well documented in several autoimmune diseases, including SLE, RA, myasthenia gravis (MG), multiple sclerosis (MS), juvenile dermatomyositis, and Sjögren's syndrome. [98][99][100][101][102][103][104] A very interesting question is why Tfh cells are specifically involved in the destruction of islet β cells but not other organs in T1D patients. One of the reasons could be the genetic susceptibility.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The Th17-like TFH cells are considered the most pathogenic and are the most effective cell type in supporting B-cell activity, particularly antibody production [ 39 ]. Importantly, another study has demonstrated that effective treatment with dimethyl fumarate results in a rebalancing of these ratios by decreasing the pathogenic Th17-like TFH cells and increasing the Th2-like TFH cells [ 63 ]. It is currently unclear how changes in these occur.…”
Section: Tfh Cells In Multiple Sclerosismentioning
confidence: 99%